2015
DOI: 10.2147/copd.s92412
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of long-acting muscarinic antagonist monotherapies in COPD: a systematic review and network meta-analysis

Abstract: BackgroundRandomized, controlled trials comparing long-acting muscarinic antagonist (LAMA) efficacy in COPD are limited. This network meta-analysis (NMA) assessed the relative efficacy of tiotropium 18 µg once-daily (OD) and newer agents (aclidinium 400 µg twice-daily, glycopyrronium 50 µg OD, and umeclidinium 62.5 µg OD).MethodsA systematic literature review identified randomized, controlled trials of adult COPD patients receiving LAMAs. A NMA within a Bayesian framework examined change from baseline in troug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
2
27
0
1
Order By: Relevance
“…Our findings also suggest consideration of several other drug classes as therapeutic candidates for PTSD. For example, acetylcholine receptor antagonists could be considered given the convergence of (1) the PheWAS association via TRAIP with Chronic Obstructive Pulmonary Disease (COPD; which can be treated with muscarinic receptor antagonists (Ismaila et al, 2015)), and (2) their association in cMAP with PLEKHM1. Angiotensin receptor antagonists, also identified as drug candidates through cMAP, have a strong preclinical rationale for use in PTSD (Marvar et al, 2014;Shekhar, 2014) and are, in fact, currently undergoing testing in a randomized placebo-controlled trial of losartan for PTSD (ClinicalTrials.gov Identifier: NCT02709018P).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggest consideration of several other drug classes as therapeutic candidates for PTSD. For example, acetylcholine receptor antagonists could be considered given the convergence of (1) the PheWAS association via TRAIP with Chronic Obstructive Pulmonary Disease (COPD; which can be treated with muscarinic receptor antagonists (Ismaila et al, 2015)), and (2) their association in cMAP with PLEKHM1. Angiotensin receptor antagonists, also identified as drug candidates through cMAP, have a strong preclinical rationale for use in PTSD (Marvar et al, 2014;Shekhar, 2014) and are, in fact, currently undergoing testing in a randomized placebo-controlled trial of losartan for PTSD (ClinicalTrials.gov Identifier: NCT02709018P).…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, в других метаанализах сравнивалась эффективность отдельных компонентов комбинированных схем терапии. Так в сетевом метаанализе, выполненном Ismaila и др., 2015, показана сопоставимая клиническая эффективность ДДАХ тиотропия и гликопиррония в стандартных дозировках, и по заключению исследователей, выбор конкретного препарата должен зависеть только от предпочтений врача и пациента [11]. Сетевой метаанализ Disse и др., 2014 г. показал сравнимую эффективность олодатерола и индакатерола в стандартных дозировках, в том числе при наличии сопутствующей терапии ДДАХ [12].…”
Section: материал и методыunclassified
“…As well as the individual clinical trials, a number of systematic reviews with meta-regression analysis of pooled data have summarised the efficacy of tiotropium in patients with COPD 19,[28][29][30][31][32][33][34] as well as its safety 35,36 . This review will not duplicate these reviews but will highlight the main findings.…”
Section: Clinical Effects Of Tiotropium In Copdmentioning
confidence: 99%
“…In a meta-analysis of these studies, aclidinium resulted in a significantly greater improvement in pre-dose FEV 1 than placebo with a mean difference of 0. 30 . The GLOW5 trial, a 12-week blinded, double-dummy study comparing glycopyrronium with tiotropium, showed no difference between the two LAMAs in their effect on trough FEV 1 , TDI and SGRQ 48 .…”
Section: Tiphon 118mentioning
confidence: 99%